Restrictive Clauses in East-West Licensing Trade: The Case of Poland - Jerzy Cieślik; Ryszard Rapacki (Economics of Planning, 1981)
The aim of this paper is to determine how contract conditions in licensing agreements between Poland and the industrialized market-economy countries influence the long-term effects of imports of modern technology. Analysis is confined to two essential aspects of this problem. The first concerns the effects of the diffusion of modern technical solutions throughout the whole economy. Unlike technology purchases by individual western enterprises, technology imports in a planned economy are considered as a source of modernization of entire branches or industries, and not only of certain enterprises. The second issue dealt with the export-promotion effect. When, after 1970, Poland launched an extensive technology importing programme, it was assumed that this would prove an essential stimulus which would in the long run change Poland's position in the international division of labour; in the short term, export growth would constitute the main source of foreign exchange needed to repay credits drawn for technology imports.
Keywords: O33; O34; 330; licenses; technology imports; licenses; technology imports